Mitigating cardiac dysfunction by TOE-guided cardioplegia and mitral valve repair. (September 2020) - Jin, Xu Yu; Sayeed, Rana; Pepper, John; Petrou, Mario
Based on current guidelines, 15% to 20% of patients undergoing mitral valve repair for regurgitation develop left ventricular dysfunction (ejection fraction < 50%–55%) despite a normal baseline. Two schools of thought have been debated: preexisting myocardial disease or suboptimal intraoperative myocardial protection. In our view, they could be reconciled. It is well recognized that left ventricular ejection fraction with a standard cut off at 50%–55% has limited sensitivity in detecting early systolic impairment in mitral regurgitation patients. Mitral regurgitation also leads to mitochondrial oxidative stress, thus rendering the myocardium more susceptible to ischemia-reperfusion injury and precipitating postoperative cardiac dysfunction. The fall in left ventricular ejection fraction early after mitral valve repair was shown to be caused by the reduction in both myocardial contractility and left ventricular stroke volume. To mitigate the risk to myocardial reperfusion injury, appropriate cardioplegia volume and distribution and well-defined surgical repair processes are equally important. We use transesophageal echocardiography-guided cardioplegia delivery, imaging the intramyocardial flow and ensuring adequate protection of the subendocardium during mitral valve repair. Mild aortic regurgitation on a beating heart often leads to left ventricular dilatation with diminished cardioplegia flow in the myocardium, thus requiring direct ostia cardioplegia. Systematic transesophageal echocardiography assessment before surgery is essential for establishing the mitral regurgitation mechanisms and translating them into precise surgical repair strategies. The benefits of transesophageal echocardiography-guided cardioplegia delivery warrant further clinical trials in order to evolve into part of a high surgical standard.